Mapping Phosphodiesterase 4D (PDE4D) in Macaque Dorsolateral Prefrontal Cortex: Postsynaptic Compartmentalization in Layer III Pyramidal Cell Circuits - Datta, Dibyadeep; Enwright, John F.; Arion, Dominique; Paspalas, Constantinos D.; Morozov, Yury M.; Lewis, David A.; Arnsten, Amy F. T. (Frontiers in Neuroanatomy, 2020)
cAMP signaling has powerful, negative effects on cognitive functions of the primate dorsolateral prefrontal cortex (dlPFC), opening potassium channels to reduce firing and impair working memory, and increasing tau phosphorylation in aging neurons. This contrasts with cAMP actions in classic circuits, where it enhances plasticity and transmitter release. PDE4 isozymes regulate cAMP actions, and thus have been a focus of research and drug discovery. Previous work has focused on the localization of PDE4A and PDE4B in dlPFC, but PDE4D is also of great interest, as it is the predominate PDE4 isoform in primate association cortex, and PDE4D expression decreases with aging in human dlPFC. Here we used laser-capture microdissection transcriptomics and found that PDE4D message is enriched in pyramidal cells compared to GABAergic PV-interneurons in layer III of the human dlPFC. A parallel study in rhesus macaques using high-spatial resolution immunoelectron microscopy revealed the ultrastructural locations of PDE4D in primate dlPFC with clarity not possible in human post-mortem tissue. PDE4D was especially prominent in dendrites associated with microtubules, mitochondria and likely smooth endoplasmic reticulum (SER). There was substantial postsynaptic labeling in dendritic spines, associated with the SER spine-apparatus near glutamatergic-like axospinous synapses, but sparse labeling in axon terminals. We also observed dense PDE4D labeling perisynaptically in astroglial leaflets ensheathing glutamatergic connections. These data suggest that PDE4D is strategically positioned to regulate cAMP signaling in dlPFC glutamatergic synapses and circuits, especially in postsynaptic compartments where it is localized to influence cAMP actions on intracellular trafficking, mitochondrial physiology, and internal calcium release.